Development E-Worksheet Based On Problem Based Learning To Improve Student's Metacognitive Ability - R. A. Mitasari; R. Hidayah (Universitas Negeri Yogyakarta, 2022)
The study aimed to determine the validity, practicality, and effectiveness of electronic student worksheets (e-worksheets) based on problem based learning (PBL) to improve students' metacognitive abilities on stoichiometric material. The research was used a research and development (R and D). The sample of the study was 30 students from SMAN 19 Surabaya. The instruments were validation sheets, student observation sheets, cognitive test sheets, and MAI questionnaires. The metacognition ability was tested using MAI questionnaire on the aspects of planning, monitoring, and evaluating. Then, it was strengthened again with a cognitive test consisting of 6 cognitive questions. The results showed that the developed e-worksheet has 89.76%; 86.67%; 83.33%; and 86.67% of content; graphics; presentation; and language validities, respectively. All components were in the very high category. The results of the practicality of the e-worksheet were 94.64%; 99.29%; 95.24%; 97.62%; and 94.05% for the PBL strategy; metacognitive; graphics; presentation; and language components, respectively. All components were in the very practical category. Based on the t-test, the sig.2-tailed of the planning, monitoring, and evaluating aspects were less than 0.05 so Ha is accepted, which means that the e-worksheet can improve students' metacognitive abilities in those aspects. This is supported by the t-test of students' cognitive abilities where the sig.2-tailed is 0.000 so Ha is accepted, which means that the developed e-worksheet can improve students' cognitive abilities